Suplementação de aminoácidos essenciais em dietas de baixo nível proteico para leitões - Toledo, Juliana Beatriz (2012)
Four experiments were carried out to evaluate the effects of reducing the crude protein levels of diets supplemented with essential amino acids on pigs performance in prestarter and starter phases. In the experiment I (performance to 6 a 15 kg) were used 120 piglets, weaned at 21 days old, with initial weight of 5.95 ± 0.33 kg and final weight of 16.17 ± 1.52 kg, distributed in a randomized block design with five treatments, eight replicates and three animals per experimental unit. The treatments consisted of five diets where the CP was reduced by 1.5% (21.0, 19.5, 18.0, 16.5 and 15.0 percentage points), meeting the requirements of amino acids with addition of L-lysine, DL-methionine, Lthreonine, L-tryptophan, L-valine and L-isoleucine. No differences were observed for performance variables with reduced CP levels in diets, ensuring that the studied levels can be used in piglets diets, since there is synthetic amino acids supplementation. The EAA: NEAA ratio increased with the reduction of protein levels, where the best ratio was 0.53 for the level of 15% CP. The urea content decreased linearly with the reduction of protein levels. In the experiment II (balance nitrogen to 6 to 15 kg) were used 20 crossbred barrow piglets (weaned at 21 days). There were two replications in time, where the average weight of piglets was 10.79 ± 2.19 kg. The piglets were housed in metabolism cages, distributed in a completely randomized design, with a total of five treatments, four replicates and the experimental unit consisted of a piglet. There was a decrease in N excretion and urea concentration in blood and urine with reduced levels of CP, which contributes to a lower N excretion to the environment. In the experiment III (performance to 15 to 30 kg) were used 60 piglets, with initial weight of 15.34 ± 0.87 kg and final weight of 30.08 ± 1.59 kg, distributed in a randomized block design with five treatments, six replicates and two animals per experimental unit. The treatments consisted of five diets where the CP was reduced by 1.5 percentage points, resulting in low protein diets (19.24%, 17.74%, 16.24%, 14.74% and 13.24%), meeting the requirements of amino acids with added L-lysine, DL-methionine, L-threonine, Ltryptophan, L-valine and L-isoleucine. The average daily gain and feed conversion ratio according to linear response plateau model (LRP) were estimated 14.23% and 14.79% of CP respectively. As the CP levels were reduced there was an increase in the EAA: NEAA ratio. The plasma urea concentration decreases in a linear effect (P<0.05), indicating that there was a better use for amino acids with the CP reduction. In the experiment IV (balance nitrogen to 15 to 30 kg were used 30 crossbred barrow piglets, with average weight of 21.69 ± 4.46 kg, housed in metabolism cages, distributed in a completely randomized design, with a total of five treatments, six replicates and the experimental unit consists of a piglet. The protein biological value in the diets remained above the ideal (70%), where the level of 13.24% CP corresponded to the highest value. There was no difference in levels of urea in blood and urine. It can be concluded that the reduction of protein levels was efficient to decrease the pollution effect in dejects, with a smaller nitrogen excretion in feces and urine.